CARICATURIZING OF SOCIAL ACTIONS IN THE PRESS A SEMIOTIC ANALYSIS (THE JAVAN NEWSPAPER OF THE İSLAMIC REPUBLIC OF İRAN) - GÖRGÜLÜ, Yusuf (Atlas Journal, 2020)
İn this study, it was emphasized how the social activity with economic indicators started in Maşhad Iran on December 28.12.2017 was caricaturized in Iranian Press. In this context, the Javan newspaper, which is preferred by the conservative wing in Iran, which is known for its proximity to the regime, will focus on how protesters, politicians are represented and in what frame they are presented, priorities and prefences. Semiotic analysis method was used as the research method. The cartoons in the newspaper were examined by Roland Barthes’ metaphor of the semantic meaning. The research was limited to the Javan newspaper. The reason why the Javan newspaper was chosen as a sample is that its a newspaper affiliated to the İslamic regime in Iran and is a more conservative newspaper in Iran as well as being an important newspaper as newspaper circulars. According to the results of the research, it was concluded that the cartoons in the Javan newspaper have made a preference for the perception of external intervention towards social actions, and by caricaturizing it, they have played an active role in the recruitment process.